2018
DOI: 10.5455/medarh.2018.72.206-209
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of Nanosil Mouthwash on the Preventing Pulmonary Infection in Intensive Care Unit: a Randomized Clinical Trial

Abstract: Introduction:Oral and Oro-pharynx colonization and Micro-aspiration of discharges are two important processes in ventilator-associated pneumonia (VAP). So, this study design to investigated the preventive effect of oral decontamination program by Nanosil mouthwash on incidence of ventilator-associated pneumonia.Methods:80 newly hospitalized patients who admitted in intensive care unit (ICU) of Amin Medical Education Center were enrolled to a randomized clinical trial study. Patients were randomly divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
2
5
1
11
Order By: Relevance
“…Male patients had 2 times the risk of having alterations throughout the hospital stay compared to the patients of female gender. This can be related to better oral hygiene practices before hospitalization and increased utilization of oral health care services among women 2,5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male patients had 2 times the risk of having alterations throughout the hospital stay compared to the patients of female gender. This can be related to better oral hygiene practices before hospitalization and increased utilization of oral health care services among women 2,5 …”
Section: Discussionmentioning
confidence: 99%
“…Some patients present oral alterations at the time of ICU admission, which might be related to a poor oral hygiene 2,5 . During hospitalization, the oral health of ICU patients is at risk due to the general medical condition of the patient and the complex treatments applied.…”
Section: Introductionmentioning
confidence: 99%
“…Outra pesquisa de ensaio clínico randomizado avaliou a eficácia de um enxaguatório bucal de Nanosil para prevenção da pneumonia associada à ventilação. Quando comparado com a clorexidina a 2%, o Nanosil revelou efeito antibacteriano de amplo espectro e mais forte sobre as bactérias orais (16) . Entretanto, quando comparada com o permanganato de potássio, a clorexidina se mostrou mais eficaz (17) .…”
Section: Discussionunclassified
“…The use of mouthwashes to prevent pneumonia is still debated. A randomized controlled trial (RCT) on 80 ICU patients who were randomized to receive Nanosil mouthwashes and chlorhexidine 0.12% for 5 days demonstrated that the pneumonia rate was reduced in the Nanosil group (2.7 vs. 23.7%, p = 0.008), but mortality was similar in both groups (88). Another trial investigating the role of peroxide hydrogen over normal saline in the prevention of pneumonia concluded that patients treated with peroxide hydrogen had a lower risk of contracting VAP (relative risk [RR], 2.6; 95% confidence interval [CI], 1.04-6.49, p = 0.0279) (89).…”
Section: Oral Hygiene and Aseptic Mouthwashesmentioning
confidence: 99%